Characterisation of haemodynamic and vascular dysfunction in bicuspid aortic valve disease using advanced cardiovascular magnetic resonance imaging techniques - Bissell, MM (2015)
Bicuspid aortic valve disease (BAV) is known to be heritable and often shows a concomitant aortopathy with increased risk of aortic dissection. This may also be present in family members. The underlying pathophysiology was largely believed to be an intrinsic aortopathy. However, recent advances in cardiovascular magnetic resonance imaging now allow in-depth haemodynamic and functional assessment of the aorta to further delineate the underlying pathophysiology. This thesis explored the association of haemodynamic and functional aortic changes with aortic dilation in BAV patients, first degree relatives and healthy volunteers. Patients with a bicuspid aortic valve were found to have an abnormal degree of helical flow in the ascending aorta with predominantly right-handed helical flow. Compared to healthy volunteers patients with a bicuspid aortic valve had larger ascending aortas, higher rotational (helical) flow, systolic flow angle and systolic wall shear stress. There were also differences between the cusp fusion patterns in BAV, with right-non coronary cusp fusion showing more severe flow and aortic abnormalities than those with a right-left coronary cusp fusion pattern: higher rotational flow, higher in-plane wall sheer stress and larger aortas respectively. BAV patients with normal flow patterns had similar aortic dimensions and wall shear stress to healthy volunteers and younger BAV patients showed abnormal flow patterns but no aortic dilation, both further supporting the importance of flow pattern in the aetiology of aortic dilation. However, aortic function measures (distensibility, aortic strain and pulse wave velocity) were similar between healthy volunteers, patients with a bicuspid aortic valve and first degree relatives with a tricuspid aortic valve. Aortic valve replacement (AVR) significantly changed the ascending aortic flow pattern in patients with a bicuspid aortic valve. The majority of patients with mechanical AVR or Ross procedure showed normal flow patterns with near normal rotational flow values post operatively and reduced in-plane wall shear stress. By contrast, all subjects with bioprosthetic AVR had residual abnormal helical flow patterns (mainly marked right-handed helical flow), with similar rotational flow values to native BAV. Wall shear stress post-bioprosthetic AVR showed a similar pattern. These findings point towards the importance of haemodynamic factors in the bicuspid aortic valve aortopathy rather than additional haemodynamic-independent mechanisms. Haemodynamic classification may allow better risk prediction and selection of patients for earlier surgical intervention. Changes in abnormal flow pattern after valve replacement could have important implications for future aortic growth, and may influence the future choice of prosthetic valves.